2008
DOI: 10.4103/0253-7613.44151
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in pharmacotherapy of glaucoma

Abstract: Glaucoma is a slow progressive degeneration of the retinal ganglion cells (RGCs) and the optic nerve axons, leading to irreversible blindness if left undiagnosed and untreated. Although increased intraocular pressure is a major risk factor of glaucoma, other factors include increased glutamate levels, alterations in nitric oxide (NO) metabolism, vascular alterations and oxidative damage caused by reactive oxygen species. Glaucoma is the second leading cause of blindness globally, accounting for 12.3% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 93 publications
0
41
0
1
Order By: Relevance
“…Disruption of this equilibrium results in raised IOP, which is an important risk factor in the pathogenesis of glaucoma, a multifactorial optic neuropathy characterized by damage to the optic nerve head and irreversible field of vision loss (Friedman et al, 2004). For this reason, most glaucoma drug treatments involve lowering IOP, either by decreasing the production of aqueous humor or by improving its outflow (Gupta et al, 2008).…”
Section: Function and Therapeutic Potential Of Nucleotides In Eyementioning
confidence: 99%
“…Disruption of this equilibrium results in raised IOP, which is an important risk factor in the pathogenesis of glaucoma, a multifactorial optic neuropathy characterized by damage to the optic nerve head and irreversible field of vision loss (Friedman et al, 2004). For this reason, most glaucoma drug treatments involve lowering IOP, either by decreasing the production of aqueous humor or by improving its outflow (Gupta et al, 2008).…”
Section: Function and Therapeutic Potential Of Nucleotides In Eyementioning
confidence: 99%
“…Most glaucoma pharmaceutical treatments involve lowering IOP, either by decreasing the production aqueous humour or by improving its outflow, thereby reducing damage of the optic nerve. [2]. Some families of compounds are currently used to induce such IOP reduction, and more are emerging as promising substances to treat this disorder [3].…”
Section: Introductionmentioning
confidence: 99%
“…It lowers IOP in both normotensive and in chronic open angle glaucoma patients. (6,7,8) It reduces IOP by 20-33%, on an average. Early trials demonstrated that it is more effective in lowering IOP as compared to epinephrine and pilocarpine.…”
Section: Introductionmentioning
confidence: 98%
“…Timolol is the US-FDA's gold standard drug for glaucoma therapy, against which all new medications must be compared prior to approval. (8) Bimatoprost, is a synthetic prostamide analog that was approved for use in US in 2001. (8,9) It lowers IOP by a dual mechanism: primarily by increasing pressure dependent (presumed trabecular meshwork) outflow, but also by increasing pressure-independent (Presumed uveoscleral) outflow.…”
Section: Introductionmentioning
confidence: 99%